PENGARUH METODE PEMBELAJARAN BERBASIS HOTS (HIGHER ORDER THINKING SKILLS) TERHADAP KEMAMPUAN PSIKOMOTORIK PRAKTIK KEPERAWATAN PADA SISWA SMKN 9 KOTA TANGERANG TAHUN 2020 - Dea Aviolita; Sulaeman Sulaeman (Nusantara Hasana Journal, 2021)
The learning and assessment process is very influential in achieving graduate competence. Graduation competencies are qualifications that are capable of graduating including skills, attitudes, and knowledge that are of national standard criteria. The skills, attitudes and knowledge possessed by students must be in accordance with the objectives of national education. There are 3 learning criteria. The first criterion of learning involves change. The second criterion of learning lasts with time. The third criterion of learning occurs through experience. Objectives: To determine the effect of HOTS (Higher Order Thinking Skills) based learning methods on the psychomotor abilities of nursing practice in SMKN 9 Kota Tangerang. Methods: The type of research used is quantitative research with research designs Pre-Experimental Designs and conducted by One-Group Pretest-Posttest Design. This study uses a non probability sampling technique that is accidental sampling with 70 respondents. The research instrument used was a questionnaire and the test analysis used was the T test. Results of research: Analysis of the T test produced Sig. = 0.941> 0.05, then H0 accepted by Ha is rejected. So it can be concluded that there is no influence or no difference between the Pre Test and Post Test which means there is no effect of the HOTS-based learning method on the psychomotor ability of practice in nursing students at SMKN 9 Kota Tangerang Year 2020. Conclusion: Based on the results of the study, there was no effect of HOTS (Higher Order Thinking Skills) based learning methods on the psychomotor abilities of nursing practice in SMKN 9 Kota Tangerang in 2020.